Uji Potensi Nefropati Diabetes Daun Sirih Merah (Piper croatum Ruiz & Pav) pada Tikus Putih Jantan (Rattus norvegicus): Potential Test of Diabetes Nefropative of Red Betel Leaf (Piper croatum Ruiz & Pav) on Male White Rats (Rattus norvegicus) - Joni Tandi; Rizaldy Lalu; Magfirah; Yunlis Silintowe Kenta; Ronaldy Nobertson (KOVALEN: Jurnal Riset Kimia, 2020)
This study aims to determine the type of secondary metabolite compounds in red betel leaf ethanol extract, the potential of red betel leaf ethanol extract on blood glucose, creatinine, and urea levels of male white rats induced by streptozotocin. This study used 30 white male rats which were divided into 6 groups: normal control, negative control, positive control, the dose of 150, 250, and 350 mg/kg BW. The showed that results ethanol extract of red betel leaves contained alkaloids, flavonoids, phenols, saponins, and tannins. Ethanol extract of red betel leaf at a dose of 150 mg /kg BW is an effective dose in reducing levels glucose blood with an average value of decreased blood glucose levels of 238.25 mg/dL, and has an effect on creatinine and ureum, with an average dose of 350 mg/kg BW with a mean creatinine level of 0.64 mg/dL and mean ureum of 39.68 mg/dL. Keywords: Creatinine, ureum, red betel leaf, streptozotocin